Application of Gum Arabic for Coating of Dried Mango Slices - Abdelgader, Mamoun Omer; Ismail, Inaam Awad (Pakistan Journal of Nutrition, 2011)
Mango (Mangifera indica) fruit of kitshenar variety which is grown in wide areas in Sudan was used in this study to investigate the effect of processing treatment and storage period on the quality of dried mango slices (finger). Mango fruits of kitshenar variety were washed carefully, peeled manually and then sliced into (fingers). Mango slices were divided into three portions, the first portion coated with (25% w/v) Gum Arabic purified solution plus (5% w/v) sugar, the second portion was treated with sodium metabisulphite solution 2000 p.p.m concentration and the third portion was left without any treatment (control). Mango slices of each treatment were speeded on aluminum trays with an equal distribution and dried at room temperature under moving fan for seven days and then the dried products were packed in (polythene) plastic socks then placed inside cartoons and stored at room temperature for nine months. The results showed that the treatment with sodiummetabisulphite solution was the best in keeping the nutritive value of mango slices (ascorbic acid). The results indicated that the best treatment which prevented browning was Gum Arabic addition. The study of the effect of storage periods at room temperature on some properties of mango slices (fingers) showed there was a marked loss of some nutrients (e.g. ascorbic acid, sugars).